2010
DOI: 10.1063/1.3415085
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the configurational temperature of polymeric liquids under shear and elongational flows using nonequilibrium molecular dynamics and Monte Carlo simulations

Abstract: Rheological and structural studies of liquid decane, hexadecane, and tetracosane under planar elongational flow using nonequilibrium molecular-dynamics simulations J. Chem. Phys. 122, 184906 (2005) We present a detailed analysis of the configurational temperature ͑T conf ͒ for its application to polymeric materials using nonequilibrium molecular dynamics ͑NEMD͒ and nonequilibrium Monte Carlo ͑NEMC͒ methods. Simulations were performed of linear polyethylene liquid C 78 H 158 undergoing shear and elongational fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In addition, the flow curves for η, Ψ 1 and the second normal stress difference, Ψ 2 = σ yy − σ zz , have been obtained and compare well with the NEMD results [299]. Baig and his co-workers [318,319] adopted a similar concept to study the viscoelasticity of polymer melts. They used an expanded Monte Carlo method as the macroscale solver for a family of viscoelastic models, which are built on the "structural" variable, x.…”
Section: Molecularly-derived Constitutive Equationmentioning
confidence: 92%
“…In addition, the flow curves for η, Ψ 1 and the second normal stress difference, Ψ 2 = σ yy − σ zz , have been obtained and compare well with the NEMD results [299]. Baig and his co-workers [318,319] adopted a similar concept to study the viscoelasticity of polymer melts. They used an expanded Monte Carlo method as the macroscale solver for a family of viscoelastic models, which are built on the "structural" variable, x.…”
Section: Molecularly-derived Constitutive Equationmentioning
confidence: 92%
“…The configurational temperature expression has been further extended for physical systems involving hard-core or discontinuous potentials [56]. Very recently, a comprehensive analysis of the fundamental aspects of the configurational temperature for nonequilibrium systems has been performed through extensive NEMD and NEMC simulations [57], suggesting that in order to define a physically meaningful configurational temperature for polymeric systems under nonequilibrium conditions, the dynamical effects created by the external fields should be excluded.…”
Section: Configurational Temperaturementioning
confidence: 99%
“…However, a more rigorous argument may be formulated in terms of a generalized ensemble. Following the procedure suggested by Ilg [58], the expression of the configurational temperature can be further generalized by applying a generalized canonical ensemble [57] such as the one adopted here-see Eqs.…”
Section: Configurational Temperaturementioning
confidence: 99%
“…There is no reason a priori that any one temperature should be a better choice than others; in fact, Ayton et al [35] established that in systems experiencing spatially varying strain rates, only Rugh's dynamical temperature is able to correctly account for the resulting heat fluxes. Several articles have reported configurational temperatures in non-equilibrium systems under shear where the temperature can feature spatial anisotropy, and di↵erences between the temperatures obtained from the kinetic and configurational routes have been reported in models of polymer fluids [36]. In a recent investigation of argon confined in zeolite structures [37], it was found that the kinetic and configurational approaches can yield significantly di↵erent results.…”
Section: Introductionmentioning
confidence: 99%